PENGARUH BERBAGAI JENIS DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH VARIETAS LEMBAH PALU - Idris Idris; Muhammad Basir; Imam Wahyudi (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2018)
Research aims to test the effectiveness of various types of manure combined with various doses of application for the growth and result of shallot varieties of Palu Valley. This research was designed using factorial randomized block design. The first factor was manure with three types of treatment, namely chicken manure (P1), got manure (P2), cow manure (P3). The second factor was the dose of manure consisting of three types of treatment, namely 10 t ha-1 (3,6 kg plot-1) (D1), 20 t ha-1 (7,2 kg plot-1) (D2), 30 t ha-1 (10,8 kg plot-1) (D3). The results show that the combination of various types of treatment and doses of chicken manure interacts on plat height parameters aged 35 days after planting. The treatment of chicken manure with a dose of 30 t ha-1 gives better results. The single treatment of chicken manure gave better results for the plant height, weight of leaves, root dry weight, leaf dry weight , number of tubers per clump. Single treatment of manure dosage of 30 t ha-1 gave better results on plant height, leaf area , leaf fres weight, leaf dry weight tuber fresh weight per hectare.